1986
DOI: 10.1126/science.233.4770.1306
|View full text |Cite
|
Sign up to set email alerts
|

A Methanotrophic Marine Molluscan (Bivalvia, Mytilidae) Symbiosis: Mussels Fueled by Gas

Abstract: An undescribed mussel (family Mytilidae), which lives in the vicinity of hydrocarbon seeps in the Gulf of Mexico, consumes methane (the principal component of natural gas) at a high rate. The methane consumption is limited to the gills of these animals and is apparently due to the abundant intracellular bacteria found there. This demonstrates a methane-based symbiosis between an animal and intracellular bacteria. Methane consumption is dependent on the availability of oxygen and is inhibited by acetylene. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
189
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(199 citation statements)
references
References 16 publications
9
189
0
1
Order By: Relevance
“…The Late Jurassic to Cretaceous bivalve Caspiconcha is regarded as chemosymbiotic because it is very large sized and very abundant at many seep deposits, and all large and abundant bivalves at modern seeps are chemosymbiotic [20,21]. While most bathymodiolin mussels have sulfur-oxidizing symbionts, some have acquired methanotrophic symbionts [22] and may thus rely only little on sulfide. However, only four to seven extant bathymodiolin species lost their sulfur-oxidizing symbionts entirely and this loss appears to be a geologically young event that took place only in early to middle Miocene time (approx.…”
Section: Methodsmentioning
confidence: 99%
“…The Late Jurassic to Cretaceous bivalve Caspiconcha is regarded as chemosymbiotic because it is very large sized and very abundant at many seep deposits, and all large and abundant bivalves at modern seeps are chemosymbiotic [20,21]. While most bathymodiolin mussels have sulfur-oxidizing symbionts, some have acquired methanotrophic symbionts [22] and may thus rely only little on sulfide. However, only four to seven extant bathymodiolin species lost their sulfur-oxidizing symbionts entirely and this loss appears to be a geologically young event that took place only in early to middle Miocene time (approx.…”
Section: Methodsmentioning
confidence: 99%
“…The volume occupied by each type of symbiont present within V. Riou et al: Bathymodiolus azoricus' carbon fixation by chemosynthesis a bacteriocyte, quantified using 3D fluorescence in situ hybridization (FISH) technique, varies from vent site to vent site between B. azoricus specimens (Halary et al, 2008). However, although physiological activity of the symbionts was observed in gills of a hydrothermal vent Bathymodiolid from the Pacific (Fiala-Médioni et al, 1986;Nelson et al 1995), in the Southern MAR B. puteoserpentis (Robinson et al, 1998) and in live specimens of the seep Bathymodiolid from the Gulf of Mexico (Childress et al, 1986;Fisher and Childress, 1992;Kochevar et al, 1992 andLee andChildress, 1995), it has to date not been demonstrated in live specimens of B. azoricus.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first discovery of a dense, unique and diverse ecosystem in deep-sea hydrothermal vents in 1977 (Corliss et al, 1979), many studies have shown that deep-sea vent invertebrates such as tubeworms and Bathymodiolus mussels are sustained nutritionally by intracellular symbiotic bacteria (endosymbionts) as primary producers (Cavanaugh et al, 1981(Cavanaugh et al, , 1987Felbeck, 1981;Childress et al, 1986). In addition, several species of deep-sea vent invertebrates harbour bacteria (epibionts) that colonize the surfaces of specialized tissues such as the dorsal setae of the polychaete Alvinella pompejana, the gill chambers of the shrimp Rimicaris exoculata and the setae of the galatheid crabs Shinkaia crosnieri, Kiwa hirsuta and K. puravida (Polz and Cavanaugh, 1995;Cary et al, 1997;Goffredi et al, 2008;Watsuji et al, 2010;Thurber et al, 2011).…”
Section: Introductionmentioning
confidence: 99%